INCREASING KNOWLEDGE OF ENTREPRENEURSHIP, MARKETING, AND CHSE AS THE DEVELOPMENT OF PINGETOURISM VILLAGE MARGA DISTRICT, TABANAN, REGENCY, BALI - I Wayan Ruspendi Junaedi; Gerson Feoh; Putu Steven Eka Putra; Budi Hidajat (Bajang Institute, 2022)
The Community Partnership Program (PKM) for Entrepreneurship, Marketing & CHSE Training and Assistance was carried out in Pinge Tourism Village, Tabanan, Bali which is located in Marga District, Tabanan Regency, Bali. The problems of the Entrepreneurship, Marketing & CHSE Training and Assistance group found that (1) Entrepreneurship was not yet available, for the pinge indigenous people (2) Marketing had not been integrated so that it could be used as a promotion for the Pinge tourism village (3) there was no center for creating interesting content regarding cultural promotion, agricultural production, and tourism. (4) There is no CHSE assistance and training in the village sector as well as procurement of facilities and materials to fulfill CHSE. To overcome this problem, the people of Pinge Tourism Village, Tabanan, Bali need a solution in the form of a PKM program in the form of the following activities: (1). Socialization of Entrepreneurship Training and Assistance, Marketing & CHSE, (2). Integrating marketing programs in a tourism village program in the form of flyers and digital marketing such as IG and FB, (3). Making promotional media (content) as digital marketing materials, and (4). CHSE assistance and training in the village sector as well as procurement of facilities and materials to fulfill the CHSE. The target achievements of PKM activities are: (1) Partners are able to have entrepreneurship knowledge > 80%, (2) Partners have marketing knowledge > 80%, (3). Partners are able to create Digital marketing content, which is applied to Instagram media, Facebook by > 50 %. (4) Partners implement CHSE according to standards and meet > 80% of self-assessment standards. PKM is designed with stages of activities which include: entrepreneurship training with business plan material, marketing training, creation of marketing promotional media (content) and procurement of facilities and materials to meet CHSE, materials for CHSE, CHSE training, CHSE independent assessment assistance. The PKM proposal is in line with one of the focuses of community service in 2022, namely tourism, specifically the development of tourism human resources who are qualified and ready to support quality tourism in accordance with the strategy of the Ministry of Tourism and Creative Economy. PKM also supports one of the leading fields of research and community service at Dhyana Pura University, namely harmonized tourism. This PKM supports the Main Performance Indicators of Higher Education: students gain experience off campus (IKU 2), lecturers engage in off-campus activities (IKU 3), and PKM activities are used as team project-based and case-based learning materials (IKU 7). The mandatory output of PKM is as a Synaptek speaker at Undhira. Additional outputs include articles in the Community Empowerment Journal (SINTA 4), publications in online media, and video publications on YouTube. This PKM program will be carried out by 3 Dhyana Pura University lecturers and involve 2 students. The implementation period is 1 year with a budget from Dhyana Pura University of IDR